Analisis Location Quotient dan Shift Share Di Kota BalikPapan Tahun 2015-2019 - Firda Auliyah Anggraeni (OPTIMAL Jurnal Ekonomi dan Manajemen, 2022)
This research is an attempt to find out the potentials that influence economic growth in Balikpapan City from 2015 to 2019. And also how big the contribution of the potential sectors is to regional economic growth. The data used is sourced from BPS.go.id or the Central Bureau of Statistics related to the GRDP (Gross Regional Domestic Product) of Balikpapan City and East Kalimantan Province on the basis of 2010 constant prices by sector in 2015-2019. By using the Location Quotient (LQ) analysis technique and the Shift Share analysis technique. The research method used by the author in this research is secondary data. With Quantitaive Analysis Method. With the aim of being able to find out the Leading Sectors or the Base and Non-Basic Sectors in BalikPapan City, what sectors make High Development Potential and Low Development Potential in BalikPapan City and the Shift Share Analysis results include Shift Interpretation, Proportional Shift (Sp) Interpretation and Shift Interpretation Differential (Sd).